Influence of "live high-train low" on hemoglobin mass and post-exercise hepcidin response in female endurance athletes - Kuorelahti T; Ihalainen JK; Linnamo V; Badenhorst C; Kettunen O; Mikkonen RS (Springer-Verlag GmbH, 2025)
Purpose: The aim of this study was to investigate the effects of a 21-day ‘live high-train low’ (LHTL) intervention on hemoglobin mass (Hbmass) and post-exercise hepcidin response in female endurance athletes. Methods: 15 national to international level female endurance athletes completed either the LHTL intervention in normobaric hypoxia (2500 m, ~ 18 h·day−1, INT, n = 7) or lived and trained in normoxia for the same duration (CON, n = 8). Tests were conducted before (PRE) and within two days after (POST) the intervention including Hbmass measurements via a carbon monoxide rebreathing method and a roller skiing skate test. Venous blood samples were collected at rest, 0, and 3 h after the aerobic exercise to test for changes in serum hepcidin, ferritin, and interleukin-6 (IL-6). Results: Normobaric hypoxia increased Hbmass (3.3 ± 1.8%, p < 0.001) in INT, while no changes were observed in CON. There were no changes in performance parameters, resting levels of hepcidin, or IL-6 from PRE to POST, but ferritin decreased in both groups (p = 0.040). Hepcidin increased 0 h post-exercise in PRE for INT (p = 0.029) and both 0 and 3 h post-exercise for CON (p = 0.001, p = 0.019). In POST elevated post-exercise hepcidin was only observed in CON (0 h, p = 0.003; 3 h, p = 0.008). Conclusions: 21-day LHTL increased Hbmass and suppressed post-exercise hepcidin response after intensive aerobic exercise. This suggests that prolonged hypoxia may induce an acute physiological response that supports iron absorption within a few days following hypoxic exposure, which may assist in achieving the aerobic adaptations sought from prolonged hypoxic training camps.
Keywords: Hepcidin; Hemoglobin mass; Normobaric hypoxia; Iron status; Infammation